2018
DOI: 10.1177/2325967118801931
|View full text |Cite
|
Sign up to set email alerts
|

Do Focal Chondral Defects of the Knee Increase the Risk for Progression to Osteoarthritis? A Review of the Literature

Abstract: Background:Focal chondral defects (FCDs) of the knee are believed to contribute to the development of osteoarthritis (OA), resulting in pain and dysfunction.Purpose:To investigate whether untreated FCDs of the knee progress to radiographically evident OA over time.Study Design:Systematic review; Level of evidence, 3.Methods:A literature review was performed by searching the PubMed, Embase, and Cochrane Library databases to locate studies evaluating clinical and/or radiological outcomes of patients with FCDs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 32 publications
1
41
0
1
Order By: Relevance
“…1c, medial). Altogether these data were consistent with previous findings indicating much more pronounced osteochondral damage and therefore more severe disease in medial condyles of patients with a varus deformity of the knee 19,21 .
Figure 1Histological assessment of tissue damage in osteoarthritic femoral condyles. ( a ) Example macroscopic (top) and microscopic (bottom) images of safranin-O stained sections illustrating the spectrum on cartilage damage in both medial and lateral condyles.
…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1c, medial). Altogether these data were consistent with previous findings indicating much more pronounced osteochondral damage and therefore more severe disease in medial condyles of patients with a varus deformity of the knee 19,21 .
Figure 1Histological assessment of tissue damage in osteoarthritic femoral condyles. ( a ) Example macroscopic (top) and microscopic (bottom) images of safranin-O stained sections illustrating the spectrum on cartilage damage in both medial and lateral condyles.
…”
Section: Resultssupporting
confidence: 90%
“…Human knee OA provides a potentially unique model for the study of MSCs in joint repair, homeostasis and OA progression. This is because the anatomical structure and biomechanical configuration of the knee is typically associated with much more severe cartilage loss on the predominantly weight-bearing medial compartment 4,1921 . The aim of this study was therefore to investigate and compare the numbers, topography and gene expression profiles of subchondral bone-resident MSCs from medial and lateral femoral condyles from the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional studies have demonstrated that regardless of their morphology, meniscus tears can predict the development of knee OA [60,61]. Similarly, in early follow up, focal cartilage lesions have led to progression of knee OA [62]. In the setting of ACL injury, the status of the meniscus and the cartilage play a big role in the development of knee OA.…”
Section: Can Acl Reconstruction Alter the Natural History Of Ptoa?mentioning
confidence: 99%
“…Focal cartilage injuries in the knee joint are a common disorder and often associated with pain and disability (Curl et al, 1997;Årøen et al, 2004;Hjelle et al, 2002;Widuchowski et al, 2007). Because cartilage lacks blood supply, it has only a very limited response to injury and thus focal defects may lead to further damage and osteoarthritis if left untreated (Marchi et al, 2019;Houck et al, 2018;Jungmann et al, 2018). Treatment options depend on factors like defect size, location and age of the patient.…”
Section: Introductionmentioning
confidence: 99%